Clinical application of non-invasive prenatal diagnosis of phenylketonuria based on haplotypes via paired-end molecular tags and weighting algorithm - Dai Peng; Zhao Ganye; Sun Gege; Xia Yanjie; Liu Ning; Kong Xiangdong (BMC Medical Genomics, 2021)
Abstract Background Phenylketonuria (PKU) is a metabolic disease that can cause severe and irreversible brain damage without treatment. Methods Here we developed a non-invasive prenatal diagnosis (NIPD) technique based on haplotypes via paired-end molecular tags and weighting algorithm and applied it to the NIPD of PKU to evaluate its accuracy and feasibility in the early pregnancy. A custom-designed hybridization probes containing regions in phenylalanine hydroxylase (PAH) gene and its 1 Mb flanking region were used for target sequencing on genomic and maternal plasma DNA (7–13 weeks of gestation) to construct the parental haplotypes and the proband’s haplotype. Fetal haplotype was then inferred combined with the parental haplotypes and the proband’s haplotype. The presence of haplotypes linked to both the maternal and paternal mutant alleles indicated affected fetuses. The fetal genotypes were further validated by invasive prenatal diagnosis in a blinded fashion. Results This technique has been successfully applied in twenty-one cases. Six fetuses were diagnosed as patients carrying both of the mutated haplotypes inherited from their parents. Eleven fetuses were carriers of one heterozygous PAH variants, six of which were paternal and five of which were maternal. Four fetuses were absence of pathogenic alleles. All results were consistent with the prenatal diagnosis through amniotic fluid. Conclusions The results showed that our new technique applied to the genotyping of fetuses with high risk for PKU achieves an accurate detection at an early stage of pregnancy with low fetal fraction in cell free DNA.